Improved field pea is more productive and provides better markets in the Ethiopian highlands - International Livestock Research Institute (International Livestock Research Institute, 2013)
Yimer Haile plants an improved field pea on his land and explains the difference between the improved and the previous one. He says the improved pea is very nice, drought and disease resistant, colorful and high yielding. The photo film is produced by the project on “Enhancing communities’ adaptive capacity to climate-change induced water scarcity in drought-prone hotspots of the Blue Nile basin, Ethiopia” (a project implemented by ILRI, UNEP and Wollo university).